Robust control of 2-axis tracking antennas using the CRONE approach. Issue 40 (2022) - Hajjem, Mohamed; Lanusse, Patrick; Victor, Stéphane; Melchior, Pierre; Thomas, Lara
Abstract: This paper presents robust control design for a mobile tracking antenna using the CRONE approach. The antenna is modeled by two coupled mechanical axes used to track azimuth and elevation angles. The parametric uncertainties of the model and the axes mechanical coupling are taken into account in the design of the position loop controller. For comparison purposes, the same control specifications are applied for a PID controller. Simulation results show the effectiveness of the CRONE controller in terms of robustness and stability, as compared to the PID.